Laju Pertumbuhan, Efektivitas, dan Kontribusi Retribusi Daerah terhadap Pendapatan Asli Daerah (PAD) Kabupaten Sigi Periode 2019-2023 - Fathia Fathia; Dwi Farradilla; Nina Yusnita Yamin; Rahayu Indriasari; Andi Chairil Furqan (Studia Ekonomika, 2025)
This study aims to determine the growth rate of effectiveness and contribution of regional levies to the original regional income of Sigi Regency during the 2019-2023 period. The method used in this study is descriptive with a quantitative approach. The results of this study indicate that the growth rate of Regional Retribution of Sigi Regency during the 2019-2023 period falls into the unsuccessful criteria with an average percentage of 29.69 percent, and the percentage continues to fluctuate, which in 2019 to 2021 decreased but increased again in 2022 to 2023. The highest growth rate percentage only reached 127.56 percent in 2023, and the lowest was -12.84 percent in 2020. Meanwhile, the effectiveness of regional retribution revenue of Sigi Regency for the 2019-2023 period continues to fluctuate, with an average percentage of 88.44 percent which falls into the fairly effective criteria. The highest percentage of effectiveness reached 100.83 percent in 2020 and the lowest percentage reached 71.78 percent in 2022. And the contribution of regional levies to PAD Sigi Regency for the 2019-2022 period falls into the very low criteria with an average percentage of 03.81 percent. The highest percentage of contribution only reached 07.64 percent in 2023, and the lowest percentage was only 02.05 percent in 2023, so the author hopes that the Sigi Regency Government will be able to increase its Regional Retribution revenues again.